KONSEKUENSI INOVASI ORGANISASI TERHADAP PERAN PR - Melati Tobing (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2011)
AbstractThe increasing levels of competition that emerged in the community, led the organizationto keep pace. It can only be achieved if the organization want to follow the changes, bydoing innovation. In doing that, an organization often have to face problems that causestagnation in the innovation process and leads to the trauma of innovation. Those obstacleswhich are not rare also happened to the communication’s activity. Therefore the role ofleadership in the organization is very important especially on how to communicate reliably.Nevertheless, a public relations strategically can support its leader in achieving innovationby acting effectively as a mediator, which is always communicate with external public andmainly with the internal’s public of the organization itself.Keywords: Organizational Innovation, Communication, Role of Public Relations